Profiling cybersecurity competition participants: Self-efficacy, decision-making and interests predict effectiveness of competitions as a recruitment tool. Issue 65 (March 2017) - Bashir, Masooda; Wee, Colin; Memon, Nasir; Guo, Boyi
Abstract: This paper presents the main results of a large-scale survey on cybersecurity competition participants in the past decade. 588 participants of the Cybersecurity Awareness Week (CSAW) competition were surveyed with measures of personality, interests, culture, decision-making and attachment styles in an exploratory study designed to identify the characteristics of cybersecurity competition participants. Subgroups analyses were performed to examine individual differences between self-proclaimed hackers and non-hackers, males and females, and cybersecurity employees versus students. Regression analyses were used to identify variables that influenced the extent to which cybersecurity competitions were effective at convincing participants to pursue a future career in cybersecurity. Cybersecurity participants who displayed higher self-efficacy, rational decision-making style, and more investigative interests were more likely to declare an interest in a career in cybersecurity after the competition.